DISCOURSE OF TOLERANCE: FRAME ANALYSIS IN BARACK OBAMA’S SPEECHES - Saulet Alpysbayeva; Valeriy Makhpirov (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The knowledge of lexical, grammatical, stylistic, and syntactic can help with political speeches allowing deconstructing the principal messages originally laid down in the address. The right uses of tolerance help to create an idea of a political leader, including based on their verbal manifestations. The use of frame analysis is relevant in modern linguistics since the world is undergoing considerable transformations. The formation of an idea of the discourse of tolerance in the modern world is necessary for every member of society, since through political texts and the introduction of implicit meanings in them, one can achieve a considerable influence on the audience. Framing analysis is the young method in the world of mass information that helps to form framing with public opinions. With this method there is the opportunity to manipulate people, when there is a potential threat or important information. The decoding of linguistic mechanisms allowed forming the main semantic, grammatical, and stylistic guidelines for the identification and interpretation of symbols, images, and meanings in a political context. The purpose of this study was to investigate the meaning of tolerance evoked by frames in particular contexts, to form the principal semantic prototypes within the political text and their structural implementation. The subject of the study was the final address of B. Obama (2016a) at the United Nations (UN) General Assembly, on September 20, 2016, considered from the standpoint of the discourse of tolerance. To understand the genealogy of the discourse of tolerance there were used other political speeches of B. Obama. For the research were used such methods as discursive (for evaluation of final address of the B. Obama speeches), linguistic (analyse of verbal constructions), contextual and frame analysis, which include such stages as content analysis to quantify tolerance, framing each form of tolerance and context analysis. Semantic elements of tolerance with practices and knowledge became the main problem of this research. In the basis of the article lie Fillmore’s views that frames activate background knowledge containing scenes and situations; scenes are related to texts; word semantics is connected with text semantics. The research is designed systematically to locate tolerance and its forms quantitatively, contextually to textual interpretation which incorporates analysis of linguistic, discursive, pragmatic, and rhetorical elements. Also, it was defined that in the speeches B. Obama used four concepts of tolerance: in positive (A) (is a product of other human value) and negative (B) (emphasizes to tolerate) meanings, verbs in passive voice (C) (direct object) and adjective (D) (describe object founded around the world). Another feature of reference is the specification of a particular type of tolerance resulting from another human virtue, i.e., respect. In this utterance conjunctions of extension: two types of variation: alternative and replacive conjunctions are used. The following groups of synonyms are distinguished: “patience”, “forbearance”, “admittance” categories, etc.; hyponyms are arranged as “superior” and “inferior” components. In componential analysis, respect is in inferior relation to tolerance. However, in current utterance, respect is in superior relation to tolerance. The complex nature of tolerance discourse, showcasing its multifaceted linguistic expression, was investigated. Through various linguistic forms and contextual cues, the tolerance frame activates scenarios of conflict and crisis, offering itself as a solution against negative trends like intolerance. The research outlined how tolerance is strategically implemented into political addresses, invoking principles of respect, diversity, equity, and human rights to address challenges, including religious conflicts and societal disparities. The results of the research further can be used to create programs for semantic prototyping, placing frame markers in automatic mode, and developing language patterns.